Pendidikan Kesehatan Manfaat Gizi Seimbang dengan Metode Pendekatan Terapi Bermain Pada Anak Usia Dini di TK Wadi Fatimah - Titin Supriatin; Ruswati Ruswati; Nurkhalifah Khumaeroh; Padya Azzahra Putri; Ilham Fauzaturrokhmani; Ade Rival; Rizky Adhitya Setiawan (Compromise Journal Community Proffesional Service Journal, 2025)
Healthy food is food that when we consume it will be able to meet nutritional needs in accordance with health standards to increase intelligence and rich healthy life (Dilla Ratih et al., 2022). Fulfillment of nutrition for early childhood is also one of the things that is important for child development. The purpose of this journal article is to analyze the effectiveness of the play therapy approach in increasing early childhood understanding of healthy food at Wadi Fatimah Kindergarten. The method used is participatory education-based socialization, which involves visual media, educational games, and hands-on demonstrations to increase children's involvement in learning. Evaluation results showed a significant increase in children's understanding of healthy food after participating in this activity. Children who previously lacked understanding of the difference between healthy and unhealthy foods began to be able to identify nutritious foods well. Educational games such as “Teman Sehat (Guess Healthy Food)” proved to be effective in attracting children's attention and improving their memory of healthy food concepts. However, there are challenges in consistently implementing healthy eating habits, especially due to influences from outside the school environment. Therefore, active involvement from parents and teachers is needed to maintain healthy eating habits in daily life.